A reputation-based announcement scheme for VANETs - Li, Qin (2013)
Vehicular ad hoc networks (VANETs) allow vehicles to generate and broadcast messages to inform nearby vehicles about road conditions, such as traffic congestion and accidents. Neighboring vehicles can utilize this information, which may improve road safety and traffic efficiency. However, messages generated by vehicles may not be reliable. We propose a novel announcement scheme for VANETs based on a reputation system that allows evaluation of message reliability. We present a secure and efficient scheme that is robust and fault tolerant against temporary unavailability of the central server.